Bowwow powwow = bagosenjige-niimi'idim - Child, Brenda J., 1959- (Minnesota Historical Society Press, 2018)
"When Uncle and Windy Girl attend a powwow, Windy watches the dancers and listens to the singers. She eats tasty food and joins family and friends around the campfire. Later, Windy falls asleep under the stars. Uncle's stories inspire visions in her head: a bowwow powwow, where all the dancers are dogs. In these magical scenes, Windy sees veterans in a Grand Entry, and a visiting drum group, and traditional dancers, grass dancers, and jingle-dress dancers -- all with telltale ears and paws and tails. All celebrating in song and dance. All attesting to the wonder of the powwow."--Provided by publisher.